ANALISIS KEPUASAN KONSUMEN RESTORAN CEPAT SAJI KENTUCKY FRIED CHICKEN (KFC) CABANG KOTA PALEMBANG - M Nasir (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2016)
Service has the great potential in forming the perceptions and attitudes of consumer toobtain satisfaction. Customer satisfaction level is determined from type of product and service thatwill be able to be worth selling if continuously gets sales increased.Customer satisfaction factor be the essential element in long-term success especially infranchise companies which working in fast food area. To be an effective fast-food company so thecompany needs to make deliveries consistent, on time, food quality and the total service. KentuckyFried Chicken Palembang branch has the standard of service quality especially for officer whodirectly interacts with consumers by making some rules in accordance with the concept of servicequality. Result of data analysis shows there is effect between services to customer satisfaction inKFC Palembang branch.